Strategi Kepolisian Resor Tidore Dalam Peningkatan Kesadaran Berlalu Lintas Pengemudi Kendaraan Bermotor Roda Dua Pada Perlintasan Jalan Taman Siswa Kota Tidore Kepulauan - Asruni Arif; Ilfan Baharuddin; Abdul Wahid Kamma (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to understand the form of the Tidore Resort police strategy in increasing awareness of the traffic of two-wheeled motorized vehicle drivers at the Taman Siswa Road Crossing, Tidore Islands City. As well as to find out the obstacle factors in implementing the Tidore Resort police strategy in increasing awareness of the traffic of two-wheeled motorized vehicle drivers at the Taman Siswa Road Crossing, Tidore City Archipelago.This study uses a qualitative method with a descriptive approach, by means of observation, interviews with 14 informants and documentation. The analysis technique used is data collection, data reduction, data presentation and conclusion.The results showed that the strategy of the Tidore Resort Police in increasing traffic awareness for drivers of two-wheeled motorized vehicles at the Taman Siswa crossroads in Tidore Islands City is still very minimal, because until now there are still many drivers who do not have awareness while driving, and the types of violations that are often It was found that the driver was not wearing a helmet. While the factor that is an obstacle in implementing the traffic police strategy is the lack of Tidore Police Traffic Unit Personnel. This situation proves that the purpose of application in the field is incompatible. This problem causes the way of prosecution and prevention in order to reduce the number of traffic violations is very minimal.